Pengembangan Desain UI/UX Aplikasi Fitmate untuk Latihan dan Rekomendasi Pemula Menggunakan Metode Design Thinking - Alexsandrea Greska; Kurniawan Dwi Irianto (Journal of Information System Research (JOSH), 2025)
The increasing public awareness of a healthy lifestyle is not always balanced with easy access to fitness guides and proper nutritional information, especially for beginners. Many fitness applications available on the market do not fully meet the personal needs of users, such as customized exercises and practical daily nutrition records. This study aims to design and evaluate a digital fitness application that provides personal exercise recommendations and daily food recording features, using the Design Thinking approach. The design process was carried out through five stages: empathize, define, ideate, prototype, and test, which allows solutions to be developed based on a thorough understanding of user needs. Design testing was carried out using the System Usability Scale (SUS) method using 10 statements covering positive and negative aspects, and involving 13 respondents consisting of personal trainers and novice users. The test results showed an average SUS score of 84.62 which is included in the "Excellent" category, indicating that this application is easy to use, relevant, and satisfying. This study proves that a user-centered approach is very effective in creating digital solutions in the field of fitness.